Hydrogen evolution from water using Mo–oxide clusters in the gas phase: DFT modeling of a complete catalytic cycle using a Mo2O4−/Mo2O5− cluster couple. Issue 36 (5th September 2016) - Ray, Manisha; Saha, Arjun; Raghavachari, Krishnan
Abstract : Hydrogen evolution from water using sacrificial reagents and Mo–oxide cluster anions has been explored. The internal energy preservation within the clusters plays a key role in the catalytic cycle. Abstract : Density functional theory (DFT) calculations using a small metal cluster couple, Mo2 O4 − /Mo2 O5 −, are used to model a complete catalytic cycle for H2 production from water. While Mo2 O4 − is known to readily react with water to form Mo2 O5 − and release H2, the principal challenge is in reducing Mo2 O5 − to Mo2 O4 − to complete the cycle. We investigate the role of several potential sacrificial reagents (ethylene, propylene, CO and acetylene) that can reduce Mo2 O5 − after the initial oxidation. DFT calculations of the free energy reaction pathways demonstrate the presence of overall kinetically accessible barriers that are below the entrance channel (separated reactants) in the Mo2 O4 − + H2 O reaction (step I) followed by the Mo2 O5 − + sacrificial reagent reactions (step II). Though the overall reaction is thermodynamically favorable, the first step is highly exothermic while the second step is endothermic. The deepest part of the potential energy surface is a complex of Mo2 O5 − with the sacrificial reagent. If the energy gained in the first reaction and the succeeding complex formation is not lost due to collisions, the subsequent barriers can be overcome, leading to possible catalytic applications of the Mo2 O4 − /Mo2 O5 − cluster couple in H2 production reactions.